Association between the neighborhood obesogenic environment and colorectal cancer risk in the Multiethnic Cohort. (October 2017) - Canchola, Alison J.; Shariff-Marco, Salma; Yang, Juan; Albright, Cheryl; Hertz, Andrew; Park, Song-Yi; Shvetsov, Yurii B.; Monroe, Kristine R.; Le Marchand, Loïc; Gomez, Scarlett Lin; Wilkens, Lynne R.; Cheng, Iona
Highlights: Among the first prospective studies of neighborhood data and colorectal cancer risk. Used a comprehensive suite of attributes to characterize the obesogenic environment. Analyzed data from the large racial/ethnically diverse Multiethnic Cohort. Traffic density was modestly associated with colorectal cancer risk among males. Abstract: Background: Information on the role of the neighborhood environment and colorectal cancer risk is limited. We investigated the association between a comprehensive suite of possible obesogenic neighborhood attributes (socioeconomic status, population density, restaurant and retail food environments, numbers of recreational facilities and businesses, commute patterns, traffic density, and street connectivity) and colorectal cancer risk in the Multiethnic Cohort Study. Methods: Among 81, 197 eligible participants living in California (35, 397 males and 45, 800 females), 1973 incident cases (981 males and 992 females) of invasive colorectal cancer were identified between 1993 and 2010. Separately for males and females, multivariable Cox regression models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for colorectal cancer risk overall and by racial/ethnic group (African American, Japanese American, Latino, white). Results: In males, higher traffic density was associated with an increased risk of colorectal cancer (HR = 1.29, 95% CI: 1.03–1.61, p  = 0.03, for quintile 5 vs. quintile 1; p -trend = 0.06). While this association may be due to chance, this pattern was seen (albeit non-statistically significant) in all racial/ethnic groups except whites. There were no other significant associations between other neighborhood obesogenic attributes and colorectal cancer risk. Conclusion: Findings from our large racial/ethnically diverse cohort suggest neighborhood obesogenic characteristics are not strongly associated with the risk of colorectal cancer.